Sex Differences in the Association between Sleep Quality and Excess Weight: Exploring Lifestyle and Health-Related Mediators - Santos, Thauanny Heslley Lima dos; Melo, Júlia Souza de; Lima, Márcia de Oliveira; Menezes, Risia Cristina Egito de; Serenini, Renan; Longo-Silva, Giovana (Sleep Science, 2025)
To compare the associations between sleep quality and body mass index (BMI), as well as excess weight status, in male and female subjects, while exploring potential mediating factors, including lifestyle and health-related variables.The present cross-sectional study analyzed data from 5,260 (29.7% male and 70.3% female) Brazilian adults collected through a virtual survey applied from 2023 to 2024. Sleep quality and duration were assessed using the Pittsburgh Sleep Quality Index (PSQI). The BMI was derived from self-reported weight and height, with excess weight defined as BMI > 24.9 kg/m2. Associations were explored using multiple linear and logistic regression models, marginal probabilities for being overweight, and restricted cubic splines. Potential mediating variables were identified through mediation analysis.Among the female subjects, poor sleep quality (β = 0.46; 95%CI: 0.15–0.77) and short sleep duration (β = 0.62; 95%CI: 0.27–0.97) were associated with higher BMI and 21% of increased odds of excess weight after adjusting for all covariates (age, depression, chronic conditions, level of schooling, marriage status, smoking, alcohol consumption, screen time before bed, physical activity, diet quality, and whether dinner is the largest meal of the day). The mediation analysis showed that chronic conditions (20%), depression (16%), and diet quality (14%) mediated the total effect of poor sleep quality on BMI in female participants. Screen time before bed was the only significant mediator for short sleep duration, accounting for ∼ 5% of the total effect. No significant associations were found in male subjects.Our findings highlight sex differences in the relationship between sleep and BMI, emphasizing the need for sex-specific approaches to sleep and weight management, focusing on health and lifestyle improvements.
Keywords: body mass index; overweight; sleep; sleep quality; lifestyle